Potentials of biogas production from young bulls manure fed with different diets - Costa, Mônica S. S. De M.; Costa, Luiz A. De M.; Lucas Junior, Jorge De [UNESP]; Pivetta, Laércio A. [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2013)
Physical and chemical characteristics of manure are modified by different animal production systems. In cattle feeding system for young bulls there is an inversion of the proportion between forage and concentrate. In other words, the animals receive a smaller amount of forage compared to the traditional system. These changes in the manure characteristics involve changes in the treatment systems. The aim of this study was to determine the potential production of biogas of batch digesters fed with manure from young bulls that received two diets containing different proportions between forage and concentrate, with or without inoculums and submitted to three levels of temperature (25, 35 and 40(0)C). The evaluated parameters were total solids (TS) and volatile solids (VS) reduction and biogas potentials production. The digesters fed with manure from animals that received the diet 2 (80%C + 20% R) showed the largest reductions of TS and VS. About the potentials of biogas production there was interaction between the factors diet and inoculums, but no effects of temperatures. The treatment content manure from animals fed with diet 2 without inoculums presented the greatest potential of biogas production per kg of TS added (0.2123 m³).

Os diferentes sistemas de criação animal no modelo industrial promovem alterações físicas e químicas nas dejeções. Na engorda de bovinos no modelo de confinamento para novilhos superprecoces, tem-se uma inversão na proporção entre volumoso (V) e concentrado (C), ou seja, os animais recebem quantidade inferior de volumoso quando comparado ao sistema tradicional de confinamento, o que implica modificações das dejeções e, consequentemente, no sistema de tratamento utilizado. Neste trabalho, objetivou-se determinar os potenciais de produção de biogás em biodigestores de bancada operados no sistema batelada, alimentados com dejetos de novilhos superprecoces que receberam duas dietas diferenciadas pelas proporções entre V e C, contendo ou não inóculo na composição do substrato e submetidos a três níveis de temperatura (25º, 35° e 40° C). Os parâmetros avaliados foram: redução de sólidos totais (ST), redução de sólidos voláteis (SV) e potencial de produção de biogás. Os biodigestores alimentados com dejetos provenientes de animais que receberam a dieta 2 (80%C + 20%V), apresentaram as maiores reduções de ST e SV. Quanto aos potenciais de produção de biogás, houve interação entre os fatores dieta e inóculo, porém não se observou efeito da temperatura. O tratamento contendo os dejetos provenientes de animais alimentados com a dieta 2, sem a utilização de inóculo, apresentou o maior potencial de produção de biogás por kg de ST adicionado (0,2123 m³).
Potenciais de produção de biogás de dejetos de novilhos superprecoces alimentados com diferentes dietas
Keywords: biodigestor batelada; níveis de temperatura; inóculo; batch digesters; temperature levels; inoculums